Integrasi Kurikulum Bahasa Arab Pesantren Tradisional dan Modern - Hasibuan, Jefri; Masrun, Masrun; Hasibuan, Nasrin (Universitas Negeri Padang, 2025)
Integrating the Arabic language curriculum between traditional and modern pesantren has become an essential discourse in responding to contemporary educational demands. Traditional pesantren emphasize mastery of Arabic through classical texts (kitab kuning) with the sorogan and bandongan methods, while modern pesantren apply structured curricula, linguistic competence, and communicative approaches. This conceptual article aims to present a theoretical exploration of integration patterns, philosophical foundations, and potential models that can harmonize these two curriculum orientations. The discussion shows that integration can be achieved through curriculum synthesis, combining classical literacy with communicative Arabic, strengthening teacher competence, and designing learning models that balance tradition and modernity. The study contributes theoretically to the development of a holistic Arabic language curriculum in pesantren.